Utility of Hybrid Transferrin Binding Protein Antigens for Protection Against Pathogenic Neisseria Species - Fegan, Jamie E.; Calmettes, Charles; Islam, Epshita A.; Ahn, Sang Kyun; Chaudhuri, Somshukla; Yu, Rong-hua; Gray-Owen, Scott D.; Moraes, Trevor F.; Schryvers, Anthony B. (Frontiers in Immunology, 2019)
The surface transferrin receptor proteins from Neisseria gonorrhoeae have been recognized as ideal vaccine targets due to their critical role in survival in the human male genitourinary tract. Recombinant forms of the surface lipoprotein component of the receptor, transferrin binding protein B (TbpB), can be readily produced at high levels in the Escherichia coli cytoplasm and is suitable for commercial vaccine production. In contrast, the integral outer membrane protein, transferrin binding protein A (TbpA), is produced at relatively low levels in the outer membrane and requires detergents for solubilization and stabilization, processes not favorable for commercial applications. Capitalizing on the core -barrel structural feature common to the lipoprotein and integral outer membrane protein we engineered the lipoprotein as a scaffold for displaying conserved surface epitopes from TbpA. A stable version of the C-terminal domain of TbpB was prepared by replacing four larger exposed variable loops with short linking peptide regions. Four surface regions from the plug and barrel domains of Neisseria TbpA were transplanted onto this TbpB C-lobe scaffold, generating stable hybrid antigens. Antisera generated in mice and rabbits against the hybrid antigens recognized TbpA at the surface of Neisseria meningitidis, and inhibited transferrin-dependent growth at levels comparable or better than antisera directed against the native TbpA protein. Two of the engineered hybrid antigens each elicited a TbpA-specific bactericidal antibody response comparable to that induced by TbpA. A hybrid antigen generated using a foreign scaffold (TbpB from the pig pathogen Haemophilus parasuis) displaying neisserial TbpA loop 10 was evaluated in a model of lower genital tract colonization by N. gonorrhoeae and a model of invasive infection by N. meningitidis. The loop 10 hybrid antigen was as effective as full length TbpA in eliminating N. gonorrhoeae from the lower genital tract of female mice and was protective against the low dose invasive infection by N. meningitidis. These results demonstrate that TbpB or its derivatives can serve as an effective scaffold for displaying surface epitopes of integral outer membrane antigens and these antigens can elicit protection against bacterial challenge.